2023
DOI: 10.1111/cbdd.14353
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective potential of formononetin, a naturally occurring isoflavone phytoestrogen

Lovedeep Singh,
Harpreet Kaur,
Girish Chandra Arya
et al.

Abstract: The increased prevalence of neurological illnesses is a burgeoning challenge to the public healthcare system and presents greater financial pressure. Formononetin, an O‐methylated isoflavone, has gained a lot of attention due to its neuroprotective potential explored in several investigations. Formononetin is widely found in legumes and several types of clovers including Trifolium pratense L., Astragalus membranaceus, Sophora tomentosa, etc. Formononetin modulates various endogenous mediators to confer neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…LRP1, the other receptor of CALR on phagocytes, has not been studied in gliomas. In Alzheimer's disease, early evidence has shown that LRP1 activation can facilitate the clearance of amyloid-β, which can be induced with formononetin treatment [78]. As such, LRP1 might represent a promising target in the CNS, but will require more preclinical studies to decipher its role in glioma cancer cell clearance.…”
Section: Discussionmentioning
confidence: 99%
“…LRP1, the other receptor of CALR on phagocytes, has not been studied in gliomas. In Alzheimer's disease, early evidence has shown that LRP1 activation can facilitate the clearance of amyloid-β, which can be induced with formononetin treatment [78]. As such, LRP1 might represent a promising target in the CNS, but will require more preclinical studies to decipher its role in glioma cancer cell clearance.…”
Section: Discussionmentioning
confidence: 99%